2011
DOI: 10.1007/s00299-011-1186-8
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas reinhardtii as a viable platform for the production of recombinant proteins: current status and perspectives

Abstract: Chlamydomonas reinhardtii has many advantages compared with traditional systems for the molecular farming of recombinant proteins. These include low production costs, rapid scalability at pilot level, absence of human pathogens and the ability to fold and assemble complex proteins accurately. Currently, the successful expression of several proteins with pharmaceutical relevance has been reported from the nuclear and the chloroplastic genome of this alga, demonstrating its usefulness for biotechnological applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 129 publications
0
59
0
2
Order By: Relevance
“…C. reinhardtii is a microalga that has importance as model for algal biofuels (11). Availability of a sequenced genome (27), molecular biology protocols (28,29), a proteomic database (25), and metabolomics protocols (30,31) benefit the exploitation of Chlamydomonas to investigate global metabolic changes in response to environmental or genetic alterations (32,33).…”
mentioning
confidence: 99%
“…C. reinhardtii is a microalga that has importance as model for algal biofuels (11). Availability of a sequenced genome (27), molecular biology protocols (28,29), a proteomic database (25), and metabolomics protocols (30,31) benefit the exploitation of Chlamydomonas to investigate global metabolic changes in response to environmental or genetic alterations (32,33).…”
mentioning
confidence: 99%
“…Numerous studies have reported the successful use of the microalga Chlamydomonas reinhardtii for production of therapeutic proteins , Muto et al, 2009, Rosales-Mendoza et al, 2012, Tran et al, 2009, Mayfield, 2013. Of particular interest are synthetic fusion proteins that combine the characteristics from different molecules to provide an enhanced physiological response (Mayfield, 2013).…”
Section: Cultivation Of Microalgae Currently Occurs In Either Open Ormentioning
confidence: 99%
“…Because of these reasons, a continuously growing number of researches have joined the BChlamy community^to study such diverse research topics as (see Citations for respective topical reviews) photosynthesis and light acclimation (Allahverdiyeva et al 2014;Heinnickel and Grossman 2013;Minagawa 2011;Rochaix et al 2012), respiration (Salinas et al 2014), flagella and basal bodies organization and function (Dutcher 2014), life cycle and mating (Umen 2011), carbon metabolism (Johnson and Alric 2013), nutrient membrane transport (Blaby-Haas and Merchant 2012;Grossman 2000), circadian clock (Matsuo and Ishiura 2011; Schulze et al 2010), photoreceptors (Kianianmomeni and Hallmann 2014), photosynthetic hydrogen Hemschemeier and Happe 2011;Melis et al 2007) and high-and low-value compound production Rasala and Mayfield 2015;Rosales-Mendoza et al 2012;Skjanes et al 2013), and many more.…”
Section: Introductionmentioning
confidence: 99%